Studying Individual Distinctions in Psychological Manifestations of Diligence of Senior Schoolchildren - G N Kameneva (Peoples' Friendship University of Russia (RUDN University), 2008)
The article considers the results of the research of the psychological structure of diligence of the senior schoolchildren carried out in the vein of A.I. Krupnov's system-functional approach.